Data Spaces for Heterogeneous Data Ecosystems – Findings from a Design Study in the Cultural Sector - zur Heiden, Philipp; Halimeh, Haya; Hansmeier, Philipp; Vorbohle, Christian; Althaus, Maike; Beverungen, Daniel; Kundisch, Dennis; Müller, Oliver (Communications of the Association for Information Systems)

Conceptualizing Digital Responsibility for the Information Age

Igniting Knowledge Management for Assistance Systems in Maintenance: A Method for Knowledge Gathering - Skolik, Alexander Marcus; zur Heiden, Philipp; Donner, Johannes Aurelius Tamino; Priefer, Jennifer (ECIS 2025 Proceedings)

Positionspapier Use Case 1: Vernetzte Kulturplattformen - Althaus, Maike; Beverungen, Daniel; Flath, Beate; Halimeh, Haya; Hansmeier, Philipp; zur Heiden, Philipp; Kundisch, Dennis; Müller, Michelle; Müller, Oliver; Oberthür, Simon; Vorbohle, Christian; Momen Pour Tafreshi, Maryam; et al.

Transforming the Digitally Sustainable Enterprise

Solutions and Technologies for Responsible Digitalization

Designing taxi ridesharing systems with shared pick-up and drop-off locations: Insights from a computational study - Stumpe, Miriam; Dieter, Peter; Schryen, Guido; Müller, Oliver; Beverungen, Daniel (Transportation Research Part A: Policy and Practice)

The Imperative of Revival Strategies through Digital Transformation in the Cultural Sector - A Taxonomy Approach - Althaus, Maike; Hansmeier, Philipp (Proceedings of the Thirty-Second European Conference on Information Systems (ECIS 2024))
Excellent Information Systems (IS) bachelor or master student theses have the potential to inform the scientific community about interesting findings about IS phenomena. However, transforming such theses into scientific working papers is not only time-consuming for the student and the supervisor, but also purely voluntary. Part of the problem is that few IS faculties offer any structured course for the transformation process as part of their curriculum. This significantly reduces the proportion of outstanding theses that are developed into working papers and, ultimately, into publications, resulting in a loss of knowledge for the broader IS community. To address this structural deficit, we aim to develop and implement a credit course and open educational resources (e.g., course schedule, slides, videos) that support students in developing their theses into publishable scientific research papers. This approach not only enriches the scientific discourse but also presents a research-oriented educational disruption for the IS community.
Keywords: Student Thesis; Scientific Publishing; Course Implementation

Paving the Way for Student-Led Publications - Development and Implementation of a Course in Information Systems with Open Educational Resources - Müller, Michelle; Althaus, Maike; Bartelheimer, Christian; Kundisch, Dennis

Designing Business Reputation Ecosystems — A Method for Issuing and Trading Monetary Ratings on a Blockchain - Hemmrich, Simon; Bobolz, Jan; Beverungen, Daniel; Blömer, Johannes (ECIS 2023 Research Papers)
Market transactions are subject to information asymmetry about the delivered value proposition, causing transaction costs and adverse market effects among buyers and sellers. Information systems research has investigated how review systems can reduce information asymmetry in business-to-consumer markets. However, these systems cannot be readily applied to business-to-business markets, are vulnerable to manipulation, and suffer from conceptual weak spots since they use textual data or star ratings. Building on design science research, we conceptualize a new class of reputation systems based on monetary-based payments as quantitative ratings for each transaction stored on a blockchain. Using cryptography, we show that our system assures content confidentiality so that buyers can share and sell their ratings selectively, establishing a reputation ecosystem. Our prescriptive insights advance the design of reputation systems and offer new paths to understanding the antecedents, dynamics, and consequences to reduce information asymmetry in B2B transactions.

Digital Responsibility – a Multilevel Framework for Responsible Digitalization - Beverungen, Daniel; Kundisch, Dennis; Mirbabaie, Milad; Müller, Oliver; Schryen, Guido; Trang, Simon Thanh-Nam; Trier, Matthias (Business & Information Systems Engineering)

Utilizing Geographic Information Systems for Condition-Based Maintenance on the Energy Distribution Grid - zur Heiden, Philipp; Priefer, Jennifer; Beverungen, Daniel (Proceedings of the 55th Hawaii International Conference on System Sciences)

Context in Design Science Research: Taxonomy and Framework - Herwix, Alexander; zur Heiden, Philipp (Proceedings of the 55th Hawaii International Conference on System Sciences)

A Renaissance of Context in Design Science Research - zur Heiden, Philipp; Beverungen, Daniel (Proceedings of the 55th Hawaii International Conference on System Sciences)

Systematizing the lexicon of platforms in information systems: a data-driven study - Bartelheimer, Christian; zur Heiden, Philipp; Lüttenberg, Hedda; Beverungen, Daniel (Electronic Markets)
Abstract While the Information Systems (IS) discipline has researched digital platforms extensively, the body of knowledge appertaining to platforms still appears fragmented and lacking conceptual consistency. Based on automated text mining and unsupervised machine learning, we collect, analyze, and interpret the IS discipline’s comprehensive research on platforms—comprising 11,049 papers spanning 44 years of research activity. From a cluster analysis concerning platform concepts’ semantically most similar words, we identify six research streams on platforms, each with their own platform terms. Based on interpreting the identified concepts vis-à-vis the extant research and considering a temporal perspective on the concepts’ application, we present a lexicon of platform concepts, to guide further research on platforms in the IS discipline. Researchers and managers can build on our results to position their work appropriately, applying a specific theoretical perspective on platforms in isolation or combining multiple perspectives to study platform phenomena at a more abstract level.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

Exogenous Shocks and Business Process Management - Röglinger, Maximilian; Plattfaut, Ralf; Borghoff, Vincent; Kerpedzhiev, Georgi; Becker, Jörg; Beverungen, Daniel; vom Brocke, Jan; Van Looy, Amy; del-Río-Ortega, Adela; Rinderle-Ma, Stefanie; Rosemann, Michael; Santoro, Flavia Maria; et al. (Business & Information Systems Engineering)
Abstract Business process management (BPM) drives corporate success through effective and efficient processes. In recent decades, knowledge has been accumulated regarding the identification, discovery, analysis, design, implementation, and monitoring of business processes. This includes methods and tools for tackling various kinds of process change such as continuous process improvement, process reengineering, process innovation, and process drift. However, exogenous shocks, which lead to unintentional and radical process change, have been neglected in BPM research although they severely affect an organization’s context, strategy, and business processes. This research note conceptualizes the interplay of exogenous shocks and BPM in terms of the effects that such shocks can have on organizations’ overall process performance over time. On this foundation, related challenges and opportunities for BPM via several rounds of idea generation and consolidation within a diverse team of BPM scholars are identified. The paper discusses findings in light of extant literature from BPM and related disciplines, as well as present avenues for future (BPM) research to invigorate the academic discourse on the topic.
Keywords: Information Systems; Business process management; Exogenous shocks; Challenges; Opportunities

From private digital platforms to public data spaces: implications for the digital transformation - Beverungen, Daniel; Hess, Thomas; Köster, Antonia; Lehrer, Christiane (Electronic Markets)
Technological developments such as Cloud Computing, the Internet of Things, Big Data and Artificial Intelligence continue to drive the digital transformation of business and society. With the advent of platform-based ecosystems and their potential to address complex challenges, there is a trend towards greater interconnectedness between different stakeholders to co-create services based on the provision and use of data. While previous research on digital transformation mainly focused on digital transformation within organizations, it is of growing importance to understand the implications for digital transformation on different layers (e.g., interorganizational cooperation and platform ecosystems). In particular, the conceptualization and implications of public data spaces and related ecosystems provide promising research opportunities. This special issue contains five papers on the topic of digital transformation and, with the editorial, further contributes by providing an initial conceptualization of public data spaces' potential to foster innovative progress and digital transformation from a management perspective.
Keywords: Digital transformation; Public data spaces; Digital platforms; GAIA-X

Systematizing the lexicon of platforms in information systems: a data-driven study - Bartelheimer, Christian; zur Heiden, Philipp; Lüttenberg, Hedda; Beverungen, Daniel (Electronic Markets)
While the Information Systems (IS) discipline has researched digital platforms extensively, the body of knowledge appertaining to platforms still appears fragmented and lacking conceptual consistency. Based on automated text mining and unsupervised machine learning, we collect, analyze, and interpret the IS discipline’s comprehensive research on platforms—comprising 11,049 papers spanning 44 years of research activity. From a cluster analysis concerning platform concepts’ semantically most similar words, we identify six research streams on platforms, each with their own platform terms. Based on interpreting the identified concepts vis-à-vis the extant research and considering a temporal perspective on the concepts’ application, we present a lexicon of platform concepts, to guide further research on platforms in the IS discipline. Researchers and managers can build on our results to position their work appropriately, applying a specific theoretical perspective on platforms in isolation or combining multiple perspectives to study platform phenomena at a more abstract level.
Keywords: Platform; Text mining; Machine learning; Data communications; Interpretive research; Systems design and implementation

Quantifying the Impact of Location Data for Real Estate Appraisal – A GIS-based Deep Learning Approach - Kucklick, Jan-Peter; Müller, Jennifer; Beverungen, Daniel; Müller, Oliver (European Conference on Information Systems)

Usage of Local Online Platforms in Retail: Insights from retailers' expectations expectations - Berendes, Carsten Ingo; zur Heiden, Philipp; Niemann, Marco; Hoffmeister, Benedikt; Becker, Jörg (Proceedings of the Twenty-Eighth European Conference on Information Systems (ECIS2020))